National Prosecutors Survey (Census), 2001 ([Verlag nicht ermittelbar], 2002)
The National Survey of Prosecutors is a survey of chief prosecutors in state court systems. It was previously conducted in 1990, 1992, 1994, and 1996 (ICPSR 9579, 6273, 6785, 2433 respectively). For 2001, instead of a survey of chief prosecutors, a census of all 2,341 chief prosecutors who handled felony cases in state courts of general jurisdiction was conducted. A chief prosecutor is an official, usually locally elected and typically with the title of district attorney or county attorney, who is in charge of a prosecutorial district made up of one or more counties, and who conducts or supervises the prosecution of felony cases in a state court system. Prosecutors in courts of limited jurisdiction, such as municipal prosecutors, were not included in the survey. The census' purpose was to obtain detailed descriptive information on prosecutors' offices, as well as information on their policies and practices. Variables cover staffing, funding, special categories of felony prosecutions, caseload, juvenile matters, work-related threats or assaults, the use of DNA evidence, and community-related activities, such as involvement in neighborhood associations. The unit of analysis is the district office.